2021
DOI: 10.1101/2021.04.06.438618
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genomic and phenotypic characterization of finger millet indicates a complex diversification history

Abstract: Advances in sequencing technologies mean that insights into crop diversification aiding future breeding can now be explored in crops beyond major staples. For the first time, we use a genome assembly of finger millet, an allotetraploid orphan crop, to analyze DArTseq single nucleotide polymorphisms (SNPs) at the sub-genome level. A set of 8,778 SNPs and 13 agronomic traits characterizing a broad panel of 423 landrace accessions from Africa and Asia suggested the crop has undergone complex, context-specific div… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 73 publications
0
1
0
Order By: Relevance
“…The cluster analysis results revealed that the subpopulations had allele admixture since some sub population had germplasm collections from more than one geographical area. Previous research reported that accessions in Subpopulations came from both southern Asia and eastern Africa (Kumar et al, 2016, Ban et al, 2021.…”
Section: Snp Characteristicsmentioning
confidence: 99%
“…The cluster analysis results revealed that the subpopulations had allele admixture since some sub population had germplasm collections from more than one geographical area. Previous research reported that accessions in Subpopulations came from both southern Asia and eastern Africa (Kumar et al, 2016, Ban et al, 2021.…”
Section: Snp Characteristicsmentioning
confidence: 99%
“…The availability of finger millet genomic resources ( Hittalmani et al, 2017 ; Hatakeyama et al, 2018 ; Zhang et al, 2019b ; Bančič et al, 2021 ; Pendergast et al, 2022 ) makes it possible to analyze different groups of genes and estimate practical methods for molecular breeding and biotechnological improvement of this crop ( Antony Ceasar et al, 2018 ; Pandian and Ramesh, 2019 ; Sood et al, 2019 ). Certainly, the identification and characterization of all CKX family members in E. coracana is a very important tool for achieving these practical goals.…”
Section: Introductionmentioning
confidence: 99%